2019
DOI: 10.1080/07391102.2018.1498804
|View full text |Cite
|
Sign up to set email alerts
|

Effects of secondary structures of DNA templates on the quantification of qPCR

Abstract: In the current design of qPCR systems, the sequences of primers are the primary concerns. The secondary structures of DNA templates have not been much considered, although they should be also critically important. In this paper, various hairpins with different stem lengths and loop sizes are placed near primer-binding sites, and their effects on the amplification efficiency of qPCR are systematically investigated. When a hairpin is formed either in the inside of the amplicon or in its outside, the amplificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…If negative controls amplify, both options permit sequencing of the amplicon to distinguish between real target detections in field samples and positive control-derived contamination. However, sequence inserts/modifications could affect tertiary structures of the DNA molecules (e.g., hairpin loops) and alter the melting temperature of and polymerase binding affinity to the template DNA (Fan et al, 2019). Great care must be taken when designing these synthetic genes to validate them in silico.…”
Section: Discussionmentioning
confidence: 99%
“…If negative controls amplify, both options permit sequencing of the amplicon to distinguish between real target detections in field samples and positive control-derived contamination. However, sequence inserts/modifications could affect tertiary structures of the DNA molecules (e.g., hairpin loops) and alter the melting temperature of and polymerase binding affinity to the template DNA (Fan et al, 2019). Great care must be taken when designing these synthetic genes to validate them in silico.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we observed that the EGFRvIII mRNA transcript contains several four guanine (4G) repeat sequences, especially close to the junction site (exon1:exon8), which is also the target region of interest. These 4G sequences have a well-documented role in the formation of G-quadruplexes as well as other 3D secondary structures (16,17), which are known to play an inhibitory role in reverse transcription and PCR amplification (18,19). Addition of PCR additives may destabilize secondary structures, as previously reported for the amplification of the highly GC-rich TERT promoter region (20).…”
Section: Introductionmentioning
confidence: 64%
“…This phenomenon may possibly be explained by efficient intramolecular hairpin formation and linear amplification of the vector backbone for linear 2i SC constructs, which would interfere with amplification of the SC amplicons, but this contingency was not investigated further. Taken together, we believe that in multiplex reactions containing both templates within the plasmid backbone we observe reduced efficiencies owing to: (a) the formation of chimeric/recombinant amplicons [24] and consequent secondary structures interfering with primer and probe binding [25] and (b) removal of primer binding sites from initial-round amplicons due to 5-3 exonuclease activity of the Hot Start TaqMan Polymerase and the relatively close proximity of the two cDNA amplicons in linear (4073 bp) and especially the circular (247 bp) 2i construct. Both of the suggested inhibitory factors, in addition to supercoiled circular conformation, were effectively minimized by using fragmented 2i SC.…”
Section: Discussionmentioning
confidence: 91%